2017
DOI: 10.3389/fphys.2017.00272
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Channels Modify TRPV1-Mediated Current Responses in Dorsal Root Ganglion Neurons

Abstract: The transient receptor potential vanilloid 1 (TRPV1) channel is highly expressed in a subset of sensory neurons in the dorsal root ganglia (DRG) and trigeminal ganglia of experimental animals, responsible for nociception. Many researches have revealed that some TRPV1-positive neurons co-express the transient receptor potential ankyrin 1 (TRPA1) channel whose activities are closely modulated by TRPV1 channel. However, it is less investigated whether the activities of TRPV1 channel are modulated by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
5
28
1
Order By: Relevance
“…Moreover, we can also speculate that since TRPA1 and TRPV1 functions may be influenced by each other [ 20 , 86 , 87 ], a re-organization in the expression and nature of these channels after nerve injury [ 88 , 89 , 90 ] enabled ADM_12 to modulate TRPV1 channels as well. Although a physical interaction between these two channels may be questionable, even if some studies described it in vitro [ 19 , 21 ], many studies reported a functional interaction between them [ 20 , 86 , 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we can also speculate that since TRPA1 and TRPV1 functions may be influenced by each other [ 20 , 86 , 87 ], a re-organization in the expression and nature of these channels after nerve injury [ 88 , 89 , 90 ] enabled ADM_12 to modulate TRPV1 channels as well. Although a physical interaction between these two channels may be questionable, even if some studies described it in vitro [ 19 , 21 ], many studies reported a functional interaction between them [ 20 , 86 , 91 , 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 is also sensitised in rat DRG immortalised neurons (50B11) in high-glucose conditions in vitro ( Hulse et al, 2015 ) and in animal models of diabetes. TRPA1 forms complexes with TRPV1, and can affect TRPV1 function, such as reducing desensitisation, thus potentially altering Ca 2+ responses ( Masuoka et al, 2017 ; Staruschenko et al, 2010 ). There is, however, no evidence that RAGE can directly alter TRPA1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in DRG neurons, the TRPV1 current densities were significantly smaller in allyl isothiocyanate (AITC)-sensitive DRG neurons than in AITC-insensitive cells and spontaneous TRPA1 channel activity inhibited the TRPV1 channels via Ca 2+ elevation (Masuoka et al, 2017). Indeed 37% of H 2 S induced Ca 2+ transients were inhibited by capsazepine which indicates mainly activation of TRPV1 receptors.…”
Section: Discussionmentioning
confidence: 99%